Triple-vector-boson processes in γγ colliders - Brandt, F. T. [UNESP]; Iboli, O. J.P. [UNESP]; Gregores, E. M. [UNESP]; Magro, M. B. [UNESP]; Mercadante, P. G. [UNESP]; Novaes, S. F. [UNESP] (American Physical Society (APS), 1994)
We study the production of three gauge bosons (W+W-Z0 and W+W-γ) at the next generation of linear e+e- colliders operating in the γγ mode. We analyze the total cross sections as well as several kinematical distributions of the final state particles. We find out that a linear e+e- machine operating in the γγ mode will produce 5-10 times more three-gauge-boson states compared to the standard e+e- mode at high energies. © 1994 The American Physical Society.